Monday
March 27, 2017

Post a New Question

Posted by on .

Show that the equation
log y = 1.54 - .008x - .658 log x
is equivalent to
y = 34.7 (1.0186)^(-x) * x^(-.658)

  • Math - Calculus - ,

    take the antilog of each side

    y= 10^(1.54-.008x-.658logx)

    y= 10^1.54 * 10^-(.008*x) * x^.658
    = 34.7((10^.008)^-x)*x^.658
    you can take it from here.

    remember log a+logb = log ab

    and a^xy= (a^x)^y

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question